2022
DOI: 10.1108/aaouj-03-2022-0031
|View full text |Cite
|
Sign up to set email alerts
|

University students' perceptions of shifting between online and offline learning: lessons from Kerala, India

Abstract: PurposeThe study explores the perspectives of college students on the pedagogical shift as well as frequent transitions between online and offline learning modes during the COVID-19 pandemic in Kerala, the most literate state in India.Design/methodology/approachA descriptive cross-sectional study was conducted among 1,366 college students in Kerala during December 2021. A pre-tested questionnaire was sent using Google Forms to students of arts and science colleges. The authors analyzed quantitative data using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…This is explained by previous study that learners are susceptible to abrupt changes in learning modes (Lei & So, 2021). Haikal was worried about his readiness for offline learning which is in line with the findings who mentioned that the students felt worried about the learning burden that might be experienced when shifting to offline class (Maya et al, 2022). Haikal was accustomed to the rhythm of online learning so he stated that he had to re-learn the offline's rhythm such as understanding the lecturer's teaching style.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is explained by previous study that learners are susceptible to abrupt changes in learning modes (Lei & So, 2021). Haikal was worried about his readiness for offline learning which is in line with the findings who mentioned that the students felt worried about the learning burden that might be experienced when shifting to offline class (Maya et al, 2022). Haikal was accustomed to the rhythm of online learning so he stated that he had to re-learn the offline's rhythm such as understanding the lecturer's teaching style.…”
Section: Discussionsupporting
confidence: 80%
“…Those conducted studies happened in order to analyze the shift from offline to online, but the move from online to offline has received less attention. On the other hand, previous study state about the transition from online learning to offline learning, yet the methodology used was a quantitative cross-sectional survey which differs from this presented study in terms of the methodology used (Maya et al, 2022). This study was intended to gather information related to the perception that students experienced during their learning transition from online to offline learning in a deeper way using a different approach which was a narrative inquiry with hope that the authorities can understand in detail what students feel.…”
Section: Introductionmentioning
confidence: 85%
“…The data from the study initiated by Curelaru et al (2022) also highlight the positive aspects of online learning and its consequential benefits, such as: convenience and accessibility, time and cost saving, psychological and medical security. The advantages of online learning identified in other studies (Maya et al, 2022;Nishimwe et al, 2022) include increased technical skills, flexibility of study time, ensuring participation in multiple educational webinars, accountability.…”
Section: Discussionmentioning
confidence: 99%
“…Educators can influence the online learning positively, but they can also have negative effects which they must be aware of in order to address them appropriately at the educational process level (Vesić et al, 2023). The transition from offline to online learning and vice versa can be difficult for students because they are required to adjust to the ever-changing learning process (Maya et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Mariadi et al [17] also added that shifting assessment administration from a traditional form to an online one can motivate lecturers in higher education to reevaluate and enhance the evaluation procedures that are novel, interesting, and useful to them. In contrast, Maya et al [18] also reported that only some students believed frequent and extensive assignments and presentations added stress to their online learning experience. Some students stated that they had lost interest in grades and marks because any students could cheat during online exams.…”
Section: Features Of Online Assessment That Students Didn't Experienc...mentioning
confidence: 94%